D313Y mutation in the differential diagnosis of white matter lesions: Experiences from a multiple sclerosis outpatient clinic. (October 2016) - Becker, Jana; Rolfs, Arndt; Karabul, Nesrin; Berlit, Peter; Kraemer, Markus
White matter lesions (WML) in younger patients might be due to a variety of neurological disorders. Fabry disease (FD), an x -linked inherited lysosomal storage disorder, happens to be misdiagnosed as multiple sclerosis (MS). In two middle-aged female patients, presenting bilateral WML, diagnosis of MS turned out to be doubtful. Human genetic analysis presented the Fabry mutation D313Y, in which clinical impact is still unclear. Disease manifestations outside the central nervous system were not detected. Our findings support the suspicion that Fabry mutation D313Y may be involved in neural damage resulting in WML.